Implicit motives, explicit traits, and task and contextual performance at work. - Lang, Jonas W. B.; Zettler, Ingo; Ewen, Christian; Hülsheger, Ute R. (Journal of Applied Psychology, 2012)
Personality psychologists have long argued that explicit traits (as measured by questionnaires) channel the expression of implicit motives (as measured by coding imaginative verbal behavior) such that both interact in the prediction of relevant life outcome variables. In the present research, we apply these ideas in the context of industrial and organizational psychology and propose that 2 explicit traits work as channels for the expression of 3 core implicit motives in task and contextual job performance (extraversion for implicit affiliation and implicit power; explicit achievement for implicit achievement). As a test of these theoretical ideas, we report a study in which employees (N = 241) filled out a questionnaire booklet and worked on an improved modern implicit motive measure, the operant motive test. Their supervisors rated their task and contextual performance. Results support 4 of the 6 theoretical predictions and show that interactions between implicit motives and explicit traits increase the explained criterion variance in both task and contextual performance.